Origin of 3 Rabid Terrestrial Animals in Raccoon Rabies Virus–Free Zone, Long Island, New York, USA, 2016–2017 - Brunt, Scott (Emerg Infect Dis, 2020)
During 2016–2017, three rabid terrestrial animals were discovered in the raccoon rabies virus–free zone of Long Island, New York, USA. Whole-genome sequencing and phylogenetic analyses revealed the likely origins of the viruses, enabling the rabies outbreak response (often costly and time-consuming) to be done less expensively and more efficiently.